Web-Based Expert System Detects Malnutrition in Toddlers with the Naïve Bayes Method - Rifki Nur Apriyono; Agung Triayudi; Ira Diana Solihati (Jurnal Mantik, 2020)
Nutrition is the supply of ingredients or food that both organisms and cells in the human body need to be able to: survive. While in the field of science and medical, nutrition may refer to: the science or practice of consumption as well the use of food. Malnutrition is a technical term commonly used in: nutrition, health, and medicine circles. Malnutrition: the condition of a person whose nutrition is below average. Symptoms of malnutrition can also be felt with following characteristics such as: fatigue, loss of appetite, impaired vision, growth and poor intellectual development too. According to the Basic Health Research in 2018, the percentage of the number of malnourished toddlers in Indonesia is: as much as 3.9% and malnutrition is: 13.8%. This study aims to detect malnutrition aged 1-5 years (toddler). This research uses: the Naïve Bayes method. In this study, there're known to be types of disease based on the symptoms, namely: Kwarshiorkor (P1), Marasmik-Kwarshiorkor (P2), Marasmus (P3) with 24 symptoms of malnutrition. With this research, it is expected to: help in the prevention of diseases and minimize the symptoms of malnutrition in toddlers.